2021
DOI: 10.3390/molecules26195789
|View full text |Cite
|
Sign up to set email alerts
|

Association of Systemic Steroid Treatment and Outcome in Patients Treated with Immune Checkpoint Inhibitors: A Real-World Analysis

Abstract: Background: Immune-related adverse events (irAEs) are inflammatory side effects, which can occur during immune-checkpoint(s) inhibitors (ICIs) therapy. Steroids are the first-line agents to manage irAEs because of their immunosuppressive properties. However, it is still debated whether or when steroids can be administered without abrogating the therapeutic efforts of immunotherapy. Methods: We retrospectively evaluated 146 patients with metastatic non-small cell lung cancer (NSCLC), melanoma and renal cell car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…Following the observed protective effect of irT on survival in the high-risk group patients, we studied the prevalence and effect on survival of additional immune-related adverse events (irAE) in the whole population and in the high-risk group. Having any non-thyroid irAE had a protective effect in the whole cohort as in previous reports [6,7,10], as did a history of treatment with high-dose steroids for irAE; this is in agreement with a recent report [29]. Other specific irAEs were not associated with survival in our cohort, possibly due to their low frequency.…”
Section: Other Iraesupporting
confidence: 92%
“…Following the observed protective effect of irT on survival in the high-risk group patients, we studied the prevalence and effect on survival of additional immune-related adverse events (irAE) in the whole population and in the high-risk group. Having any non-thyroid irAE had a protective effect in the whole cohort as in previous reports [6,7,10], as did a history of treatment with high-dose steroids for irAE; this is in agreement with a recent report [29]. Other specific irAEs were not associated with survival in our cohort, possibly due to their low frequency.…”
Section: Other Iraesupporting
confidence: 92%
“…One study of 156 patients examined OS in patients who received glucocorticoids within 30 days or after 30 days of initiation ICIs for irAEs. This study showed no association in glucocorticoid use and overall survival and a possible improved outcome for those who started steroids after 30 daysalthough this is prone to immortality bias (15). A separate retrospective study including 257 patients who received steroids for irAEs showed decreased overall survival if glucocorticoids were initiated within two months of ICI onset after adjusting for glucocorticoid indication including tumor site, brain metastases, and the type of irAEs (14).…”
Section: Use Of Glucocorticoids At Onset or Early On After Initiating...mentioning
confidence: 68%
“…Use of glucocorticoids to treat irAEs The associated effects of glucocorticoids on cancer outcomes when used for the treatment of irAEs is difficult to interpret. While glucocorticoids may mitigate the immune effects of ICIs, irAEs themselves may be a prognostic marker for enhanced tumor response to ICIs (15). Ideally, the comparison of outcomes between patients with the same irAEs treated with and without glucocorticoids in a clinical trial would provide more clarity but has obvious ethical considerations, as these agents are recommended as first-line treatment for irAE in clinical practice guidelines (3)(4)(5).…”
Section: Use Of Glucocorticoids At Onset or Early On After Initiating...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, mixed evidence exists as to whether the use of systemic corticosteroids decreases the effectiveness of ICIs. [84][85][86][87][88] One of the most salient features of cutaneous irAEs is their significant impact on prognosis. 89 MAV, whether arising spontaneously or as a result of ICIs, has been well established as a predictor of favourable outcomes and good prognoses.…”
Section: Implications Of Cutaneous Immune-related Adverse Eventsmentioning
confidence: 99%